Effects of Hsp90 Inhibitor Ganetespib on Inhibition of Azole-Resistant Candida albicans - Yuan, Rui; Tu, Jie; Sheng, Chunquan; Chen, Xi; Liu, Na (Frontiers in Microbiology, 2021)
Candida albicans is the most common fungal pathogen. Recently, drug resistance of C. albicans is increasingly severe. Hsp90 is a promising antifungal target to overcome this problem. To evaluate the effects of Hsp90 inhibitor ganetespib on the inhibition of azole-resistant C. albicans, the microdilution checkerboard method was used to measure the in vitro synergistic efficacy of ganetespib. The XTT/menadione reduction assay, microscopic observation, and Rh6G efflux assay were established to investigate the effects of ganetespib on azole-resistant C. albicans biofilm formation, filamentation, and efflux pump. Real-time RT-PCR analysis was employed to clarify the mechanism of antagonizing drug resistance. The in vivo antifungal efficacy of ganetespib was determined by the infectious model of azole-resistant C. albicans. Ganetespib showed an excellent synergistic antifungal activity in vitro and significantly inhibited the fungal biofilm formation, whereas it had no inhibitory effect on fungal hypha formation. Expression of azole-targeting enzyme gene ERG11 and efflux pump genes CDR1, CDR2, and MDR1 was significantly down-regulated when ganetespib was used in combination with FLC. In a mouse model infected with FLC-resistant C. albicans, the combination of ganetespib and FLC effectively reversed the FLC resistance and significantly decreased the kidney fungal load of mouse.